Structural response of a floating runway excited by the taking off of an airplane (Journal of Naval Architecture and Marine Engineering, 2014)
When designing a floating airport we need to address the structural response both by ocean waves and dynamic loads such as the landing / take off of an airplane. Since such problems are not conducive to physical modeling and experimental validation due to their size and speeds involved, numerical analysis is an accepted norm. However conventional means to study structural responses using a three dimensional runway with time varying dynamic loads is numerically difficult and time consuming. The analysis is made simpler by assuming the airport to be a simple, infinitely long beam, given by a one dimensional Timoshenko-Mindlin plate equation, in contact with the water surface. In developing this expression, a Fourier transformation in space in wave number domain is utilized rather than using the wave propagation method to reduce the analysis to a substructure. On analyzing, the structural response is seen as local peaks emanating from the point of load application which moves in a curvilinear path with increasing speed of the airplane. The location of these peaks a priori is however not feasible.DOI: http://dx.doi.org/10.3329/jname.v11i2.19167